Desenvolvimento, validação e confiabilidade de uma escala de dor aguda pós-operatória em asininos (equus asinus) - Oliveira, Maria Gláucia Carlos de (2019)
This study aimed to identify donkey behaviors indicative of acute pain and from these behaviors refine and validate a scale to assess acute pain in these animals. Forty-four adult donkeys underwent castration following intravenous (IV) xylazine sedation, induction with glyceryl guaiacol and thiopental IV ether, local anesthetic block and maintenance with isoflurane. The animals were monitored by videos that were watched to record all body language expressed by the donkeys. The scale was constructed from these videos, associated with pain behaviors described for horses, followed by content validation. The scale was evaluated by three blinded evaluators and one gold-standard observer through preoperative and postoperative edited videos, which comprised: three to four hours after anesthetic recovery, between 5 and 6 hours after recovery. anesthetic (2 hours after analgesic rescue with flunixin - 1.1 mg / kg, dipyrone - 10 mg / kg and morphine - 0.2 mg / kg IV) and 24 hours after surgery. Content validity, sensitivity, specificity, and responsiveness of behaviors were used to refine the scale. Intra and interobserver reliability was determined by weighted Kappa coefficient, criterion validity by comparing the proposed scale with the visual analog scale (VAS), internal consistency by Cronbach's α coefficient, item-total correlation by Spearman coefficient and analgesic rescue score. by the operating characteristics of the receiver curve and Youden index. The main behavior related to donkey pain was the elevation of the pelvic limb. The scale presented very good intraobserver reliability (0.88 - 0.96), interobserver reliability ranged from good to moderate (0.56 - 0.66), showed responsiveness for all items, good criterion validity. VAS (0.75), acceptable internal consistency (0.64), and except for neck position and head direction, adequate item-total correlation and according to principal component analysis, good association between items. The accuracy of the analgesic rescue point was excellent (area under the curve = 0.91). The analgesic rescue score was ≥ 3 out of 11 points. UFERSA-Unesp can diagnose and quantify acute pain in donkeys submitted to castration, as the instrument is reliable and valid, with a defined intervention analgesic score